The mitogenome of the sunken wood limpet Notocrater youngi: insights into mitogenome evolution in Lepetellida (Gastropoda: Vetigastropoda). (27th April 2022) - Uribe, Juan E; Sei, Makiri; Harasewych, M G
ABSTRACT: The complete mitochondrial genome of the pseudococculinid limpet Notocrater youngi was determined using Illumina sequencing and found to be a double-stranded circular molecule 15, 915 bp in length. It contains the usual 13 protein-coding genes, 2 ribosomal RNA genes and 22 transfer RNA genes, although with a gene order that differs from those of all other presently known Vetigastropoda, and that is derived within Lepetellida. Phylogenetic analyses based on amino acid sequences join the three pseudococculinid species in a clade and confirm the well-supported clade Scissurelloidea + (Lepetelloidea + Lepetodriloidea) but not a monophyletic Lepetellida as currently understood. Patterns of gene order rearrangements are concordant with these findings.